2018
DOI: 10.1021/acs.jafc.8b04487
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and Transport Characteristics of Tyrosol Acyl Esters in Rat Intestine

Abstract: Lipophenols such as palmitoyl esters of green-tea polyphenols (GTP) have been allowed for use as food additives for oxidation control. However, their digestive absorption remains unexplored. In this paper, the hydrolysis and transport characteristics of tyrosol acyl esters (TYr-Es) with various fatty acids (C12:0, C14:0, C16:0, C18:0, C18:1, and C18:2) were evaluated using the everted-rat-gut-sac model for the first time. HPLC-UV measurements demonstrated that TYr-Es were hydrolyzed to TYr, which contributed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…However, this is not to say that the triester derivatives of resveratrol cannot be used as antioxidant supplement, cosmetic, or pharmaceuticals ingredients. The esterified phenolics may be hydrolysed by the microorganism, biased pH, and enteric/in vivo enzymes under specific physiochemical or physiological environments [ 41 , 46 ]. Depending on the acyl chain length and degree of acylation, they may be rapidly hydrolysed, detoxified, and excreted from the human body before/after entering systemic circulation and act as antioxidants in this process [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not to say that the triester derivatives of resveratrol cannot be used as antioxidant supplement, cosmetic, or pharmaceuticals ingredients. The esterified phenolics may be hydrolysed by the microorganism, biased pH, and enteric/in vivo enzymes under specific physiochemical or physiological environments [ 41 , 46 ]. Depending on the acyl chain length and degree of acylation, they may be rapidly hydrolysed, detoxified, and excreted from the human body before/after entering systemic circulation and act as antioxidants in this process [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research showed that resveratrol fatty acid esters (RSv-Es) and tyrosol fatty acid esters (TYr-Es) were stable in simulated gastric fluid 15 and could be hydrolyzed to free polyphenol by intestinal lipase in an everted-rat-gut-sacs model. 16,17 Furthermore, when administered orally to rats, TYr-Es exhibited a prolonged plasma half-life compared to that of TYr. 18 Another study indicated that free hydroxytyrosol (HTy) was liberated from hydroxytyrosol acetate (HTy-Ac) by pancreatin.…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosol is one of the most abundant phenolic compounds found in olive oil (Richard et al 2011) and the presence of tyrosol esters in olive oil was more recently documented (Lee et al 2016). Furthermore, the esters of tyrosol were found to undergo hydrolysis in rat gut sac model, hence releasing tyrosol to render its effects (Yin et al 2018). However, the biological functions of lipophilic tyrosol esters are not yet well elucidated.…”
Section: Discussionmentioning
confidence: 99%